A case of sclerosing angiomatoid nodular transformation with central calcification - Eri Nakamura, MD; Yasutaka Ichikawa, MD, PhD; Kensuke Domae, MD; Yuzuna Aoki, MD; Yoichi Kozaki, MD; Miki Usui, MD; Akito Taniguchi, MD; Motonori Nagata, MD, PhD; Hajime Sakuma, MD, PhD (Radiology Case Reports)
Sclerosing angiomatoid nodular transformation (SANT) is a rare benign vascular disease and mostly discovered incidentally in asymptomatic patients. Since SANT grows over time and it is often difficult to rule out malignancy on imaging, splenectomy is frequently the treatment of choice. Image findings of SANT have been reported as low signal intensity on T2-weighted magnetic resonance (MR) images and a characteristic enhancement pattern on dynamic contrast-enhanced computed tomography (CT) and MR images. This report describes a case of a 43-year-old woman with SANT presenting multiple calcifications on CT images, and discusses the characteristics and mechanism of the calcification, while reviewing previously reported cases of SANT.